1969
DOI: 10.1128/aem.18.5.744-747.1969
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic and Related Enzymes in Clostridial Classification

Abstract: The activities of 15 glycolytic and related enzymes were determined in clostridia. All contained 1-phosphofructokinase; three of them lacked 6-phosphofructokinase and mannitol 1-phosphate dehydrogenase. Glucose 6-phosphate dehydrogenase was found in six clostridia, thus demonstrating the presence of hexose monophosphate shunt. Only parts of the citric acid cycle were found to be present in most clostridia with an indication of the full cycle in Clostridium septicum. The intermediary enzyme activities were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…To our knowledge, gluconokinase and 6-phosphogluconate dehydratase have not been observed in these bacteria. The enzymes of the hexose monophosphate pathway, glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase, are present in a number of clostridia, however, in small amounts only (6,8,9).…”
mentioning
confidence: 99%
“…To our knowledge, gluconokinase and 6-phosphogluconate dehydratase have not been observed in these bacteria. The enzymes of the hexose monophosphate pathway, glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase, are present in a number of clostridia, however, in small amounts only (6,8,9).…”
mentioning
confidence: 99%
“…The need for more rapid bacterial species identification, especially with genera associated with food-borne illness, is quite apparent. Several novel methods, including immunological and enzymatic, have been proposed (14). The present investigation suggests that principles of immunochemistry and gas chromatography can also be combined and utilized in this respect.…”
Section: Methodsmentioning
confidence: 88%
“…The lipid portions of C. botulinum types A, B, and E were found to contain essentially the same fatty acids but in different concentrations. Tetradecanoic (C: 14) and hexadecanoic (C:16) acids were found to be the predominant fatty acids in the whole cell extracts of types A, B, and E. Together they make up over 50% of the total fatty acids. Table 1 lists the fatty acids identified in the five microorganisms studied.…”
Section: Methodsmentioning
confidence: 99%
“…C. butyricum lacks all the necessary enzymes to completely metabolise citric acid, as it contains only NADP-specific isocitrate dehydrogenase (ICDH) and not L-malate dehydrogenase (MDH). 36 Another recent study found that C.…”
Section: Synthesis Of Glycerol Gelsmentioning
confidence: 99%